Australian mobile broadband network performance: Mobile apps as one possible way to provide consumer information - Evans, Shara (Journal of Telecommunications and the Digital Economy, 2014)
This paper explores the ways in which consumers gain information about mobile network performance and coverage, then examines the factors that impact mobile performance, and the challenges affiliated with representing results, which are highly influenced by transient events. The paper then discusses the role that mobile speed test apps and crowdsourcing initiatives can play in measuring mobile broadband performance, and provides an analysis of how the features and methodologies of eight major speed test applications compare and contrast. Lastly, the paper provides a brief review of the US Government’s Broadband Mapping Program; and some closing thoughts on lessons for Australia, and in particular how a crowdsourcing initiative could complement the recently announced 100m Mobile Coverage Programme.